Efforts to Improve Student Learning Outcomes Using Visual Media in Mathematics Subjects for Class IV Students at SD Negeri 1 Genggelang Academic Year 2022/2023 - Sopiatun, Eno; Fitriana, Arum Maulida (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to improve student learning outcomes through the use of multiplication and decimal division boards in multiplication and decimal division material for Class IV students at SD Negeri 1 Gengelang, Gangga District. This research was carried out in the classroom on class IV students in the second semester of the 2022/2023 academic year with a population of 16 students and 1 class teacher. This type of research is classroom action research in the form of collaboration carried out over 2 cycles. The research design used Zainal Aqib's classroom actions which consisted of 4 stages; planning, implementation, observation and reflection. Data on student learning outcomes was collected through observation sheets and pre-test and post-test student learning outcomes in Mathematics, multiplication and division of decimals. The data that has been collected is analyzed descriptively qualitatively. The results of the research showed that the student learning outcomes in cycle I included 6 students who completed (37.5%), and 10 students who did not complete (62.5%) with an absorption capacity of 38%. and in the second cycle the number of students who completed it was 15 people (93.75%), and 1 student who did not complete it (6.25%) with an absorption capacity of 94%.